Stomatopod Crustacea of Lord Howe Island - Ahyong, Shane T. (Zootaxa, 2022)
Prior to the present study, five species in four genera of the mantis shrimp superfamily Gonodactyloidea were known from Lord Howe Island, Australia. The 2017 Australian Museum expedition to Lord Howe Island made a small but significant collection of stomatopods, comprising four species: Chorisquilla tweediei (Serène, 1950), Gonodactylaceus falcatus (Forskål, 1775), Pseudosquilla ciliata (Fabricius, 1787) and a new species of Acaenosquilla, representing the first record of the superfamily Lysiosquilloidea from Lord Howe Island. The new species of Acaenosquilla is formally described and a key to the stomatopods of Lord Howe Island is provided.